A marketing resource-based model of international market entry and expansion for professional services firms - Laird, Kenneth R; Kirsch, Robert J; Evans, Thomas G (Services Marketing Quarterly, 2003)
This paper examines the entry of the Big Six international accounting firms, into emerging foreign markets and explores marketing resource considerations once established in those markets. The study is based on survey data (supplied by the Big Six) regarding their penetration of the People's Republic of China, the Commonwealth of Independent States, and Central Europe. The paper presents a marketing resource-based model based upon relevant research. The model focuses on firm specific resource capabilities interacting with the foreign business environment and the foreign intrafirm structure as a determinant of foreign market entry choice and eventual market expansion. The research findings broaden our understanding of factors that influence professional services firms' development of marketing resource strategies when expanding globally. While all firms surveyed offered a full range of services, their marketing resource strategy differed from domestic approaches because of various local constraints on marketing mix elements. © 2003 Taylor & Francis Group, LLC.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-289-840-256-573 tex.type: [object Object]
Keywords: Commonwealth of Independent States; Eastern European and Baltic states; International market entry and expansion; International marketing of accounting services; Marketing mix strategies of professional services firms; People's Republic of China; dept.acc; dept.mkt